2007
DOI: 10.1111/j.1365-2958.2007.05811.x
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome segregation control by Escherichia coli ObgE GTPase

Abstract: SummaryEscherichia coli cells depleted of the conserved GTPase, ObgE, show early chromosome-partitioning defects and accumulate replicated chromosomes in which the terminus regions are colocalized. Cells lacking ObgE continue to initiate replication, with a normal ratio of the origin to terminus. Localization of the SeqA DNA binding protein, normally seen as punctate foci, however, was disturbed. Depletion of ObgE also results in cell filamentation, with polyploid DNA content. Depletion of ObgE did not cause l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
56
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(60 citation statements)
references
References 75 publications
3
56
1
Order By: Relevance
“…On the other hand, the results of three separate studies indicated that Obg, as well as its orthologs in many bacteria, is required for the assembly of the 50S subunit, [48][49][50] even though it has been found in E. coli that ObgE (an Obg ortholog) plays a direct role in chromosome segregation and that the ribosome assembly phenotype is a secondary effect. 51) In addition, Obg co-elutes with the ribosome and is bound specifically to ribosomal protein L13, together with other factors that are involved in the general stress response. 52) These results suggest that Obg might monitor the physiological status of the ribosome (and/or DNA replication) and then control the initiation of sporulation via the phosphorelay pathway, as well as regulating the assembly of the ribosome in order to provide sufficient amounts of active ribosomes in sporulating cells.…”
Section: The Existence Of Ribosome-associated Proteins During Sporulamentioning
confidence: 99%
“…On the other hand, the results of three separate studies indicated that Obg, as well as its orthologs in many bacteria, is required for the assembly of the 50S subunit, [48][49][50] even though it has been found in E. coli that ObgE (an Obg ortholog) plays a direct role in chromosome segregation and that the ribosome assembly phenotype is a secondary effect. 51) In addition, Obg co-elutes with the ribosome and is bound specifically to ribosomal protein L13, together with other factors that are involved in the general stress response. 52) These results suggest that Obg might monitor the physiological status of the ribosome (and/or DNA replication) and then control the initiation of sporulation via the phosphorelay pathway, as well as regulating the assembly of the ribosome in order to provide sufficient amounts of active ribosomes in sporulating cells.…”
Section: The Existence Of Ribosome-associated Proteins During Sporulamentioning
confidence: 99%
“…Our genetic analysis also identified ObgE as a function required for survival of replication inhibition and suggested that ObgE may control replication fork stability, chromosome organization, or segregation (Foti et al 2005(Foti et al , 2007. Viable hypomorphic mutants in obgE were synthetically lethal with those negating doublestrand break repair (Foti et al 2005) and have modest over-replication and asynchronous replication phenotypes.…”
Section: Discussionmentioning
confidence: 95%
“…Foti et al (7) isolated an obgE mutant that was sensitive to various replication inhibitors, like hydroxyurea (HU). Further studies by the same group showed that ObgE is required for cell cycle progression in E. coli (8). Sato et al (25) recently showed that ObgE is associated with several ribosomal proteins.…”
mentioning
confidence: 99%
“…To demonstrate the essentiality of cgtA in the V. cholerae ⌬relA strain, we performed similar spot dilution assays, and the results corroborated the results obtained with V. cholerae strain NcgtA13 (data not shown). It should be mentioned that very recently two different groups working on the stringent response and cgtA gene function of E. coli failed to isolate an E. coli ⌬cgtA ⌬relA double mutant (8,13). Altogether, it appears that the cgtA gene is essential in a relA mutant background in both V. cholerae and E. coli.…”
mentioning
confidence: 99%
See 1 more Smart Citation